RFCAG2013: Russian-Finnish comparison of absolute gravimeters in 2013 - Mäkinen J. (Journal of Geodetic Science, 2016)
In June–July 2013,we performed a comparison of five absolute gravimeters of different types. The gravimeters were the FG5X-221 of the FGI, the FG5-110 and GBL-M 002 of the TsNIIGaiK, the GABL-PM of the IAE SB RAS, and the GABL-M of the NIIMorGeofizika (Murmansk, Russia). The three last-mentioned are field-type portable gravimeters made by the Institute of Automation and Electrometry in Novosibirsk, and this is the first international comparison for them. This Russian-Finnish Comparison of Absolute Gravimeters RFCAG2013 was conducted at four sites with different characteristics: at the field sites Pulkovo and Svetloe near St. Petersburg, and at the laboratory sites TsNIIGaIK in Moscow and Zvenigorod near Moscow. At the TsNIIGAiK site and at Zvenigorod two piers were used, such that altogether six stations were occupied. The FG5X- 221 provides the link to the CCM.G-K2 Key Comparison in Luxembourg in November 2013. Recently, the Consultative Committee for Mass and Related Quantities and the International Association of Geodesy drafted a strategy on how to best transmit the results of Key Comparisons of absolute gravimeters to benefit the geodetic and geophysical gravimetric community. Our treatment of the RFCAG2013 presents one of the first practical applications of the ideas of the strategy document, andwe discuss the resulting uncertainty structure. Regarding the comparison results, we find the gravimeters show consistent offsets at the quite different sites. All except one gravimeter are in equivalence.